Power scaling of high-power linearly polarized fiber lasers with <10 GHz linewidth - Chu, Qiuhui; Shu, Qiang; Li, Fengyun; Guo, Chao; Yan, Yuefang; Zhang, Haoyu; Liu, Yu; Tao, Rumao; Lin, Honghuan; Wang, Jianjun (Frontiers in Physics, 2023)
In this work, an all-fiberized polarization-maintained (PM) fiber laser has been demonstrated with a near-top-hat-shaped spectrum. By optimizing the modulation signal to generate near-top-hat-shaped spectrums, a 3-kW PM fiber laser has been achieved at <10 GHz linewidth with the polarization extinction ratio of 96% and beam quality of 1.156, which is the highest output power ever reported with approximately 10 GHz linewidth, and further scaling of output power is limited by stimulated Brillouin scattering. By decomposing the mode content, the proportion of the fundamental mode in the output laser is above 97%. The stimulated Raman scattering suppression ratio reaches 62 dB at the maximal output power.